TECNOLOGIA SOCIAL NA PREVENÇÃO DA MORTALIDADE MATERNA, FETAL E INFANTIL - Roos, Maclaine de Oliveira (2022)
Despite advances in the qualification of comprehensive care for Children's and Women's Health, we still have the majority of maternal, fetal and infant deaths resulting from preventable causes. Objectives: This paper aims to describe the process of implantation and implementation of the Committee for the Prevention of Maternal, Fetal and Infant Mortality as a social technology to reduce preventable causes of death, including Congenital Syphilis - SC, and to demonstrate whether there is underreporting of SC as cause of death, emphasizing the magnitude of this problem. Methodology: Research that integrates a Social Technology-TS. Initially, an experience report was carried out describing the creation of the product Regional Committee for the Prevention of Maternal, Fetal and Infant Mortality-CPMMFI, at the 4th Regional Health Coordination-4thCRS, in Rio Grande do Sul-RS. This experience included the following stages: Mobilization of the maternal and child network in the region; Formation of the driving group of the stork net; Conducting the situational diagnosis and signaling the “critical nodes” to prevent maternal, fetal and infant mortality; Implementation of the regional committee; Elaboration of the committee operationalization regiment; Conducting periodic meetings; Need to create a technical group; Analysis of cases from the investigation files; Creation of an epidemiological bulletin; Creation of the death surveillance protocol and holding of workshops for the prevention of maternal, fetal and infant mortality. Based on the committee's discussions, a quarterly newsletter was created. After that, a methodological research was carried out to create the protocol-type product that took place in five stages: 1st stage- Identification of the problem and justified analysis with the team involved, which consisted of the mobilization of professionals representing institutions and maternal health care units fetal and infant. 2nd stage- Research in the national and international literature- A search for scientific evidence was carried out that addressed the weaknesses in the health care of women, pregnant women and the fetus. 3rd stage Preparation of the Protocol. 4th stage- Evaluation of the Protocol by the professionals involved in the investigation and the Committee, which was carried out through a questionnaire using a 5-point Likert scale (strongly disagree, partially disagree, neutral, partially agree, fully agree) which consisted of questions about objectives, structure, clarity, relevance and applicability of the protocol. The questions evaluated were divided into three domains: objectives (3 questions), structure and clarity of presentation (2 questions) and relevance and applicability (3 questions). All questions presented a percentage of agreement above 96%, considering total or partial agreement. The Action research to develop a workshop-type product included four: 1st phase: Identification and justified analysis of the problem with the team involved; 2nd phase: The methodological course of organization of the Maternal, Fetal and Child Mortality Investigation workshop. 3rd phase- Operationalization of the Workshop. The observational, retrospective, quantitative research was carried out to search for data recorded in SIM, and in SINAN, referring to perinatal deaths, SG and SC of residents in the municipalities of the 4th Regional Health Coordinator of the State Secretary of Health of Rio Grande do Sul (4th CRS/SESRS) in the period from 2015 to 2019. This coordinator is one of the 18 Regionals of the State, responsible for two health regions and constituted at the time of 32 municipalities in the central region of the State with a population of about 541,000 inhabitants. The population consisted of fetal deaths and early neonatal deaths, which constitute perinatal mortality and cases reported as SG and SC. Results:The data from this research show the need to discuss, with health proessionals, the causes of death, both preventable and non-preventable. This educational and non-punitive reflection calls for rethinking reality, behaviors, what was done, what was not done and what could have been done differently to avoid maternal, fetal and infant death. Social technology was signaled by the movement carried out from the products mentioned, such as the creation of the newsletter that met the information needs for the Municipalities that are part of the 4th CRS. The CRMMFI Research Protocol for professionals to understand the concepts applied in surveillance of these deaths in order to notify and investigate in the best way, thus qualifying the information. These products meet the demands of the service and were based and anchored in scientific evidence and clinical knowledge. Final considerations: Social technology and its applicability met the demands and objectives of this research. All the activities carried out and the studies described, originated from a multidisciplinary work with a lot of dedication and partnership of the different sectors. The movement created and its repercussions encouraged professionals to rethink their daily practice, as well as invest in the search for knowledge that favors the quality of services and thus maternal and child health.